Response to Szutta, Dominiak, Wojda, and Lipski on Evictionism - Block, Walter (Roczniki Filozoficzne, 2025)
I am very grateful to Professors Artur Szutta, Łukasz Dominiak, Paul Wojda and Piotr Lipski for commenting on my essay “Evictionism, Pro-life and Pro-choice,” published in this issue. I have been writing about evictionism as an alternative to the well-known attempts to solve the conundrum of abortion for many decades. I have not made much headway in publicizing this viewpoint to the present date. It is my hope that these four splendid essays will rectify that deficiency. More important, the reactions of these four eminent philosophers have forced me to look far more deeply into my own writings on this subject. None of the four have yet seen their way clear to embrace this viewpoint. It is my hope that this response of mine will set them on this path.